RHIZOCTONIA SPECIES FROM STRAWBERRY PLANTS IN ERZINCAN, TURKEY: ANASTOMOSIS GROUPS AND PATHOGENICITY - T. G. Kesimci; E. D. Durak; E. Demirci (Journal of Animal and Plant Sciences, 2022)
This study was carried out to determine anastomosis groups and pathogenicity of 166 Rhizoctonia isolates obtained from strawberry plant samples in Erzincan province, Turkey during 2009 and 2010. Rhizoctonia species and anastomosis groups (AGs) of all the isolates were determined using classical techniques. Molecular characterizations of the selected Rhizoctonia isolates were performed by sequence analysis of the internal transcribed spacer (ITS) regions of the ribosomal DNA (rDNA). Of these, 155 isolates were identified as binucleate (BN) Rhizoctonia spp., and 11 isolates were as multinucleate (MN) Rhizoctonia solani. Three BN Rhizoctonia isolates were identified as Ceratobasidium albasitensis, the remaining BN Rhizoctonia isolates were assigned to AG-A (54 isolates), AG-E (11 isolates), AG-G (37 isolates), AG-H (6 isolates), AG-K (44 isolates). Rhizoctonia solani isolates were classified as AG-2-1 (4 isolates), AG-4 HGII (3 isolates) and AG-5 (4 isolates). Pathogenicity test was conducted on strawberry plants (cv. Fern), and AG-G isolates were found to constitute the highest disease severity than other species or AGs of Rhizoctonia obtained in this study. BN Rhizoctonia AG-E, R. solani AG-5 and C. albasitensis were first time reported on strawberry plants in Turkey.
Keywords: Anastomosis group; black root rot; Ceratobasidium albasitensis; rDNA-ITS region; Rhizoctonia; strawberry